Psychometric properties of Persian Version of Belongingness Orientation Scale - Saeidi Rezvani, Talieh; Tanhaye Reshvanloo, Farhad (International Journal of Education and Cognitive Sciences, 2022)
It seems that human-being has an intrinsic need for belongingness. Belongingness has multiple strong effects on emotional patterns, cognitive processes, and optimal psychological functioning. This study aimed to investigate the psychometric properties of the Belongingness Orientation scale in Iranian students. In a descriptive-correlational study, 300 students (60.3% female; age mean=20.54±1.70) from Birjand University were selected by multistage random sampling method. Participants completed Belongingness Orientation Scale (Lavigne et al., 2011) and Interpersonal Orientation Scale (Hill, 1987). Data were analyzed by confirmatory factor analysis, Pearson`s correlation coefficient, and MANOVA using SPSS.25 and Amos.24 software. Confirmatory factor analysis confirmed the two-factor structure. Factor loading varied from 0.65 to 0.87. The results showed that there are significant relationships between the dimensions of belongingness orientation and interpersonal orientation. Correlation coefficients varied from 0.37 to 0.51. Cronbach’s alpha coefficients are 0.79 for two subscales. Split-half coefficients are 0.70 for growth orientation and 0.74 for deficit reduction orientation. It seems that the Belongingness Orientation scale has good construct validity and reliability in students. This scale can be used as a precise instrument in this regard.